INTERACTIVE CONTENT DI INSTAGRAM STORIES DAN BRAND RECALL: PERAN MEDIASI CUSTOMER ENGAGEMENT PADA BRAND KULINER LOKAL SYARAH BAKERY DI KOTA BENGKULU - Yayan Shaputra; Andi Azhar (UM. Bengkulu, 2026)
This study aims to analyze the influence of interactive content in Instagram Stories on brand recall with the role of customer engagement mediation in local culinary brand Syarah Bakery in Bengkulu City. The type of research used is quantitative research with accidental sampling techniques. The research sample consisted of 100 Syarah Bakery consumers in Bengkulu City. Data was collected through questionnaires using the Likert scale and analyzed using the Partial Least Square (PLS) method. The results showed that interactive content in Instagram Stories had a significant positive effect on brand recall (path coefficient = 5.389; p-value = 0.0000,). Interactive content on customer engagement was not significant (path coefficient = 269; t-statistic = 2.169; p-value = 0.030). The mediation of customer engagement between interactive content and brand recall was not shown to be significant (t-statistic = 3.483 and p-value 0.000. This research suggests that Syarah Bakery continues to develop engaging interactive content and build communication strategies that can increase customer engagement to strengthen brand recall and grow customer buying interest. Kata Kunci: Interactive Content, Brand Recall, Customer Engagement